IRAP маркеры в оценках дифференциации сортов риса - Глазко, В.И.; Цветков, И.А.; Иванов, А.Н. (Видавничий дім "Академперіодика" НАН України, 2007)
The comparative analysis of amplification product spectra, which were obtained with the use of PawS5, PawS6 and PawS11, the end fragments of retrotransposon-like elements of family R173, as primers in 14 rice varieties, was carried out. The data on the expressive differentiation between rice varieties by the combination of amplification products with different lengths of DNA fragments were obtained. The possibility to use these fragments for the genetic identification of rice varieties is demonstrated.